PENGEMBANGAN MODUL PEMBELAJARAN FISIKA BERORIENTASI SETS PADA MATERI LISTRIK DINAMIS UNTUK MENINGKATKAN KEMAMPUAN BERFIKIR KRITIS SISWA - Purwandari Purwandari; Farida Huriawati; Andista Candra Yusro; Rofik Tri Wibowo (IKIP PGRI MADIUN, 2014)
This research aims to (1) acquire the form of the development of physics oriented learning module SETS (2) Determine the increase studens critical thinking skills after participating physics module SETS result oriented evelopment. The research was conducted in MAN 1 Madiun, with the sample and the population of student of class X. Trial conducted in small class and large class. Used technique of data collection is open questionnaire, pre test ang post test. Pre-requisite test result of analysis is the test of normality Liliefors and homogeneity Bartlett. Result of test analysis instrument using validity, reliability, level of difficulty and different power problems. Result of this research are (1) the result of the assessment carried out by the validator to the development of product obtained an average score of 3,21,considered feasible (2,8 < X 3,4). Result of student responses when small class test showed a good response with an average score 3,28 and an average score 3,23 in the limited class test,then the product is appropriate to the student's response. (2) increase student critical thinking abilities showed moderate improvement, it can be seen from the average of n-gain obtained 0,6 (0,3 < g0,7). (3)conclusion of development SETS based modules to improve critical thinking ability equivalent high school student on the topic of dynamic electricity decent quality for use by the user in the learning process.